10. PROGNOSTIC VALUE OF LACTATE CLEARANCE COMBINED WITH APACHE II SCORE IN PATIENTS WITH SEVERE SEPSIS AND SEPTIC SHOCK (Vietnam Journal of Community Medicine, 2025)
Objective: To evaluate the prognostic value of lactate clearance combined with APACHE II score in patients with severe sepsis and septic shock.Methods: A prospective cross-sectional analytical study was conducted on 80 patients with severe sepsis and septic shock in the Intensive Care Unit, Hue Central Hospital from June 2023 to October 2024. Blood lactate levels and APACHE II scores were measured at T₀ (ICU admission), T₆ (6 hours after T0), and T₂₄ (24 hours after T0). ROC curve analysis was performed to assess mortality prediction value.Results: Mean age was 63.34 ± 16.82 years with 56.3% males. Septic shock prevalence was 81.2% and mortality rate was 68.7%. Lactate levels and APACHE II scores were significantly higher in non-survivors compared to survivors at T₆ and T₂₄ (p < 0.05). The best prognostic value belonged to lactate clearance combined with APACHE II score at T₂₄ with area under ROC curve = 0.911 (95% CI: 0.85-0.97), sensitivity 85.5% and specificity 88%. Multivariate regression analysis identified APACHE II T₂₄ (OR = 1.33; p < 0.05) and lactate T₂₄ (OR = 1.96; p < 0.05) as independent mortality predictors.Conclusion: Lactate clearance combined with APACHE II score demonstrates high prognostic value for patients with severe sepsis and septic shock, particularly at 24 hours after ICU admission.
Keywords: Severe sepsis; septic shock; lactate; APACHE II; mortality prediction.